Should Silent Reading feature in a secondary school English programme? West Australian students' perspectives on Silent Reading - Merga, Margaret (2013)
The purpose of my article is to provide an opportunity for reflection on the merit of incorporating Silent Reading into secondary learning programmes. The role of Silent Reading in the learning programme has been the subject of recent research, yielding mixed findings. I explore the current issues that have arisen in research which warrant the consideration of practitioners, with a particular focus on adolescent learners. These issues are subsequently examined in light of findings from the recent West Australian Study in Adolescent Book Reading. Qualitative data from semi-structured, dyadic interviews were gathered and analysed, with the reflections of students providing insight into the current status of Silent Reading in secondary schools, and the efficacy of elements of contemporary models of Silent Reading. © 2013 National Association for the Teaching of English.